'Gulag' mentality that is holding us back - Abd Razak, Dzulkifli (2009)
THE declaration of Sept 16 as a national holiday which happened quite close to the eve of the 20th anniversary of the fall of the Berlin Wall on Nov 9, 1989 has special significance to Malaysians all over the country. Although unlike the neighbouring cities of East and West Berlin, divided by a manmade barrier, Peninsular Malaysia and Sabah and Sarawak are on two land masses separated naturally by a deep blue ocean. While their German counterparts, Berliners in particular, faced unimaginable tragedies for almost three decades, Malaysians on either sides are spared such agonies.